2019
DOI: 10.1186/s12889-019-7729-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships between parent experiences and youth self-reports of slapping/spanking: a population-based cross-sectional study

Abstract: BackgroundSlapping/spanking is related to a number of poor health outcomes. Understanding what factors are related to the increased or decreased use of spanking/slapping is necessary to inform prevention. This study used a population-based sample to determine the prevalence of slapping/spanking reported by youth; the relationship between sociodemographic factors and slapping/spanking; and the extent to which parental exposures to victimization and maltreatment in childhood and current parental mental health, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…More specifically, consistent with the current work, data from parents and adolescents from Ontario, Canada indicated that a parent’s history of experiencing slapping/spanking and emotional abuse were related to an increased likelihood that their child or youth would be slapped/spanked, while parental physical neglect was not related to children’s experiences of spanking in either study [ 42 ]. Importantly, parental experiences of physical abuse demonstrated reverse relationships in each study with the current study finding an increased likelihood with their child experiencing spanking and the Ontario data indicating decreased likelihood with their child experiencing slapping/spanking [ 42 ]. It is possible that growing up in a violent household may lead to a tolerance of violence and the continued use of physical force across generations.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…More specifically, consistent with the current work, data from parents and adolescents from Ontario, Canada indicated that a parent’s history of experiencing slapping/spanking and emotional abuse were related to an increased likelihood that their child or youth would be slapped/spanked, while parental physical neglect was not related to children’s experiences of spanking in either study [ 42 ]. Importantly, parental experiences of physical abuse demonstrated reverse relationships in each study with the current study finding an increased likelihood with their child experiencing spanking and the Ontario data indicating decreased likelihood with their child experiencing slapping/spanking [ 42 ]. It is possible that growing up in a violent household may lead to a tolerance of violence and the continued use of physical force across generations.…”
Section: Discussionsupporting
confidence: 76%
“…However, what is currently not well understood is how parents’ history of a wider range of individual ACEs may be related to an increased likelihood of their own children being spanked. One study from our group using representative data from Ontario, Canada indicated that a parents’ childhood experiences of being bullied, slapped/spanked, experiencing sexual abuse, emotional abuse, and exposure to physical intimate partner violence (IPV) were associated with increased odds of youth reports of being spanked or slapped, while parents’ childhood experiences of physical abuse were associated with a decreased likelihood of youth reports of being spanked or slapped [ 42 ]. More work is needed in this area with a focus on a broader range of specific ACEs experienced by parents and how this may be related to the intergenerational transmission of violence with their own children’s experiences of spanking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research using the same sample found that 18% of adolescents aged 14 to 17 years had reported being spanked on the bottom and/or slapped on the hand 3 times or more in their lifetime. 19 Information on missing data is available in Appendix A .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of parents/caregivers were biological, adoptive, or stepparents (88.4% mothers, 9.7% fathers), and the remaining 1.4% were related or unrelated caregivers. 19 Study methods are published elsewhere. 37 Only adolescents aged 14 to 17 years were asked questions about lifetime spanking/slapping and child maltreatment, and therefore, this subsample was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation